2017
DOI: 10.1016/j.invent.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

User characteristics and usage of an open access moderated internet support group for depression and other mental disorders: A prospective study

Abstract: BackgroundInternet support groups (ISGs) for mental ill-health are common but little is known about the characteristics of users, the usage and predictors of ISG usage and if and how these change over time.AimThis study evaluated the attributes of a publically accessible ISG for depression and other mental disorders including: (1) the demographic and other characteristics of its users; (2) their patterns of usage; and (3) the factors which predict posts to and retention on the ISG.MethodUser characteristics (g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Research nevertheless suggests that peer support can improve outcomes such as quality of life and hope [4,20], increase social network and wellness [21], and reduce treatment costs and rates of re-hospitalization [17]. While much of the literature on peer support is based on offline face-to-face settings, online peer support has evolved rapidly in recent years [22,23], also for mental health issues [24] exemplified through different types of interventions and target groups [25][26][27]. An online support group or community is defined as "any virtual social space where people come together to get and give information or support, to learn, or to find company" [28].…”
Section: Introductionmentioning
confidence: 99%
“…Research nevertheless suggests that peer support can improve outcomes such as quality of life and hope [4,20], increase social network and wellness [21], and reduce treatment costs and rates of re-hospitalization [17]. While much of the literature on peer support is based on offline face-to-face settings, online peer support has evolved rapidly in recent years [22,23], also for mental health issues [24] exemplified through different types of interventions and target groups [25][26][27]. An online support group or community is defined as "any virtual social space where people come together to get and give information or support, to learn, or to find company" [28].…”
Section: Introductionmentioning
confidence: 99%
“…The convenience of access from home can mean that for some support such as for weight loss, online forums can provide better support than face-to-face help (Hwang et al, 2011). For those living in rural areas, gaining online connections is beneficial as it may be otherwise difficult to find (Griffiths et al, 2017). Chan et al (2016) found that forum use can help participants understand and empathize with others in their positions or to help deal with rejection that they felt from people in real life (Bailey et al, 2017).…”
Section: Online Communities As Peer Supportmentioning
confidence: 99%
“…In many of these environments, anonymity and social modeling are crucial components that govern and guide behavior and allow individuals to feel comfortable expressing their emotions, concerns, and opinions publicly. Investigations of other online environments where help-seeking traffic is common and the incorporation of open access internet support forums that are moderated would contribute to our understandings about behaviors across genres (Griffiths, Carron-Arthur, Reynolds, Bennett, & Bennett 2017;McKiernan, Ryan, McMahon, & Butler, 2017). Further, this Note.…”
Section: Discussionmentioning
confidence: 98%
“…In many virtual environments, individuals interact with anonymity, which seems to provide a variety of social benefits ranging from security and privacy to behavioral change such as an increased propensity to openly engage in social activity. This security and privacy can lead to positive interactions where individuals feel free to discuss personal health or social issues (Fox & Duggan, 2013), and actively seek help and advice from others on open-access, moderated internet support forums (Griffiths, Carron-Arthur, Reynolds, Bennett, & Bennett 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation